Process-driven SOA : patterns for aligning business and IT - Hentrich, Carsten (Infosys Press, 2012)
"This book provides guidance on how to design and build software architectures that follow principles of business-IT alignment. The authors illustrate the design process step-by-step, using proven patterns that address complex business/technical scenarios, where integrated concepts of SOA, Business Process Management, and event-driven architectures are required. Providing a hands-on guide to process-driven SOA, the text describes how to manage the complexity of business-aligned IT architecture with examples and industry cases"--Provided by publisher.